(3CSGSjGJ GdJehjd hGdEOGQI GdeGdjI (B/s - (3Mfaj, YHO GdZaGQs; (3bQjGbU, QSejI Rcj s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2004)
(3ebOeI aj GdGOGQI GdeGdjI(B-(3OhQ GdhXjaI GdeGdjI ddeTQhY,GdJNWjW ddESJKeGQ aj GdCUhd GdQCSeGdjI,bQGQGJ GdJehjd WhjdI GdCLd,GdJMdjd GdeGdj hGdJNWjW hGdQbGHI,GdJNWjW GdeGdj hGdQbGHIs
(3HHdjhZQGajG(B:(3U(B.191:(3U(B.411-415s
Keywords: (3GdGOGQI GdeGdjIs; (3GdGSJKeGQs; (3GdJehjds